Creation and Implementation of a Multidisciplinary Pediatric Hematopoietic Stem Cell Transplant Discharge Coordination Program - Jessica D. Murphy; Kathryn Duke; Cambree J. Fillis; Heather J. Symons (Nursing Reports, 2025)
Background/Objectives: Hospital discharge of pediatric hematopoietic stem cell transplant (HSCT) patients is complex and requires multidisciplinary efforts to ensure patients/caregivers are prepared for transition to the outpatient setting. This period is tenuous as patients are medically complex, immunocompromised, and required to take several medications requiring dose titration. Miscommunication or decreased preparedness for discharge can place patients at risk for life-threatening complications. An integrative review was performed to evaluate the current literature on discharge coordination best practices for pediatric HSCT, revealing a scarcity of data. Taking into account this minimal literature and the lack of an established process at our center, this article details the development and implementation of a multidisciplinary care coordination program for pediatric HSCT patients following hospital discharge, aiming to establish a standardized approach and thus improve caregiver readiness for discharge. Methods: A group of physicians, advanced practice nurses, registered nurses, and pharmacists developed a comprehensive approach to pediatric HSCT discharge coordination. Interventions included standardized education, checklist integrated into the electronic medical record, 24 h rooming-in period, and personalized pharmacist follow-up. Surveys were provided to caregivers to assess discharge readiness and ongoing medication adherence. Results: This quality improvement project demonstrated feasibility via successful implementation for 12 patients. Compared to a nine-patient pre-implementation group, there was no statistically significant difference in perceived readiness. Medication adherence was unable to be evaluated. Clinical significance was anecdotally appreciated by the medical care team, with improved organization, collaboration, and communication. Conclusions: A new pediatric HSCT discharge coordination program was created and successfully implemented. More literature on best practices is needed.